Effects of Selenium with Vitamin E and Melatonin on Cadmium-Induced Oxidative Damage in Rat Liver and Kidneys - Kara, Haki; Cevik, Aydin; Konar, Vahit; Dayangac, Alpaslan; Servi, Kadir (Humana Press Inc, 2008)
The present study was performed to determine the protective effects of melatonin alone and vitamin E with selenium combination against cadmium-induced oxidative damage in rat liver. A total of 60 male rats were equally divided into five groups, one of which acted as control receiving subcutaneous injections of physiological saline. The remaining four groups were treated with subcutaneous injections of cadmium chloride at a dose of 1 mg/kg weight. The first study group received no treatment. The second group was treated with a combination of 60 mg/kg vitamin E and 1 mg/kg sodium selenite. Group 3 was treated with 10 mg/kg melatonin, and the four group received a combination of vitamin E, sodium selenite, and melatonin at the doses mentioned above. After 1 month, the animals were killed, and liver and kidneys were excised for histopathological inspection and determination of tissue malondialdehyde and the activity of superoxide dismutase. The animals receiving no treatment showed significantly higher malondialdehyde levels and reduced activity of superoxide dismutase (p<0.05). Treatment with antioxidants resulted in a significant reduction in malondialdehyde when compared to nontreated animals (p<0.05) and increase in the enzyme activity that was almost the same as the controls. The pathological findings were also in parallel with the results of the biochemical analysis. In conclusion, all the agents tested had protective effects against cadmium-induced oxidative damage.
Keywords: Cadmium; Melatonin; Selenium; Vitamin E; Oxidative damage; Rat tissue